2009
DOI: 10.1111/j.1540-6520.2009.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming the Boss: Discretion and Postsuccession Success in Family Firms

Abstract: Family firms can enjoy substantial longevity. Ironically, however, they are often imperiled by the very process that is essential to this longevity. Using the concept of managerial discretion as a starting point, we use a human agency lens to introduce the construct of successor discretion as a factor that affects the family business succession process. While important in general, successor discretion is positioned as a particularly relevant factor for productively managing organizational renewal in family bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 73 publications
1
87
0
1
Order By: Relevance
“…28 Finally, the role of succession planning could be considered to better illuminate the concept of innovation during leadership succession. The degree to which the roles of both predecessor and successor are explicitly defined (Lansberg, 1988;Mitchell et al, 2009) seems to impact the perception of this phase as an opportunity rather than a threat. Thus, the degree to which responsibilities and tasks will be clearly divided between both generations is able to provide the successor with room for the needed innovation activities (Mitchell et al, 2009).…”
Section: Limitations and Future Researchmentioning
confidence: 96%
See 2 more Smart Citations
“…28 Finally, the role of succession planning could be considered to better illuminate the concept of innovation during leadership succession. The degree to which the roles of both predecessor and successor are explicitly defined (Lansberg, 1988;Mitchell et al, 2009) seems to impact the perception of this phase as an opportunity rather than a threat. Thus, the degree to which responsibilities and tasks will be clearly divided between both generations is able to provide the successor with room for the needed innovation activities (Mitchell et al, 2009).…”
Section: Limitations and Future Researchmentioning
confidence: 96%
“…Fourth, while starting with the owner-managers' perspective and perceptions has its own merits, it would be fruitful to investigate the next generation's perspective, skills, abilities, and motivation in the context of innovation (Mitchell et al, 2009). 27 Our supplementary analysis revealed that owner-managers seem to attribute a higher suitability of the succession phase for innovation activities if a family internal successor holds experience from outside the focal industry.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…When the family firm is managed by the first generation, the founder occupies a central position within the organization, which grants him/her sufficient power to drive a behavior that coincides with his/her own business vision (Gedajlovic et al, 2004). Therefore, firms at the founder stage have a greater freedom of action thanks to the power and legitimacy concentrated in the figure of the founder (Mitchell, Hatt, Valcea, & Towsend, 2009), and this tends to go hand in hand with a centralized organizational structure, in which decisions are taken rapidly and which suits the firm's entrepreneurial behavior (Chrisman, Chua, & Steier, 2003). Schulze, Lubatkin, and Dino (2003) also state that family businesses at the founding stage have a higher propensity for incurring debt.…”
Section: Generational Level Environment and Eomentioning
confidence: 97%
“…Inertial forces, which help firms to replicate themselves on a daily basis and to follow previously successful strategies (Hannan and Freeman 1984), may limit succeeding generations' ability to exploit their innovations. Because succeeding generations tend to focus on conserving family wealth, they often institutionalize ''best practices,'' and thus innovation becomes less important to their success (Mitchell et al 2009). That is, these firms have been established long enough to have developed a solid customer base and reputation in the industry that can sustain firm performance simply by following tried and true practices and through word-of-mouth.…”
Section: The Moderating Role Of Innovativenessmentioning
confidence: 98%